1953
DOI: 10.1113/jphysiol.1953.sp004936
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the lungs of the new‐born lamb

Abstract: In a previous series of experiments it was shown that artificial positive pressure ventilation of the lungs of foetal lambs caused an immediate fall of pulmonary and systemic arterial blood pressures (Ardran, Dawes, Prichard, Reynolds & Wyatt, 1952). In three lambs the systemic arterial pressure recovered, while the pulmonary arterial pressure continued to fall towards the level commonly found in adult animals. The observations of Reynolds, Ardran & Prichard (1953) on pulmonary circulation time in these newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
154
2
2

Year Published

1961
1961
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(165 citation statements)
references
References 4 publications
(4 reference statements)
6
154
2
2
Order By: Relevance
“…The results, shown in Table 1, make it clear that, by 12 hr, pulmonary artery pressure was less than the high values recorded by Dawes, Mott, Widdicombe & Wyatt (1953) in the mature sheep foetus but, by the eighth day, they were still higher than the low levels reported by Reeves, Grover & Grover (1963) in the lamb a few weeks old. These intermediate values are similar in range to those given by Adams & Lind (1957), Eldridge & Hultgren (1955) and by , in the new-born infant of comparable age.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The results, shown in Table 1, make it clear that, by 12 hr, pulmonary artery pressure was less than the high values recorded by Dawes, Mott, Widdicombe & Wyatt (1953) in the mature sheep foetus but, by the eighth day, they were still higher than the low levels reported by Reeves, Grover & Grover (1963) in the lamb a few weeks old. These intermediate values are similar in range to those given by Adams & Lind (1957), Eldridge & Hultgren (1955) and by , in the new-born infant of comparable age.…”
Section: Resultsmentioning
confidence: 76%
“…However, their calculations, using the Fick quotient, would, in the presence of a left-to-right shunt, overestimate the pulmonary A-V difference and underestimate the true pulmonary flow. This could be more than a trifling error since Dawes et al (1953) had previously shown that normally the left-to-right shunt could contribute up to 50 % of pulmonary flow. If, in their series, the sequence was that found in this study, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…After birth, with initiation of ventilation by the lungs, and the subsequent increase in pulmonary and systemic arterial blood oxygen tensions, pulmonary vascular resistance decreases and pulmonary blood flow increases by 8-10-fold to match systemic blood flow (1)(2)(3)(4). This process is regulated by a complex and incompletely understood interplay between mechanical and metabolic factors (5).…”
Section: Introductionmentioning
confidence: 99%
“…This process is regulated by a complex and incompletely understood interplay between mechanical and metabolic factors (5). For example, the replacement of fluid with gas in the alveoli changes alveolar surface tension, which unkinks the small pulmonary arteries, and causes an immediate decrease in pulmonary vascular resistance and increase in pulmonary blood flow (2,5). There is also release of vasoactive substances, such as prostacyclin (PGI 2 ), which decrease pulmonary vascular resistance and increase pulmonary blood flow (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation